Identification of Malassezia furfur Secreted Aspartyl Protease 1 (MfSAP1) and Its Role in Extracellular Matrix Degradation - Si En Poh; Joleen P. Z. Goh; Chen Fan; Wisely Chua; Shi Qi Gan; Priscilla Lay Keng Lim; Bhavya Sharma; David I. Leavesley; Thomas L. Dawson; Thomas L. Dawson; Hao Li (Frontiers in Cellular and Infection Microbiology, 2020)
Malassezia is the most abundant eukaryotic microbial genus on human skin. Similar to many human-residing fungi, Malassezia has high metabolic potential and secretes a plethora of hydrolytic enzymes that can potentially modify and structure the external skin environment. Here we show that the dominant secreted Malassezia protease isolated from cultured Malassezia furfur is an aspartyl protease that is secreted and active at all phases of culture growth. We observed that this protease, herein named as MfSAP1 (M. furfur secreted aspartyl protease 1) has a broader substrate cleavage profile and higher catalytic efficiency than the previously reported protease homolog in Malassezia globosa. We demonstrate that MfSAP1 is capable of degrading a wide range of human skin associated extracellular matrix (ECM) proteins and ECM isolated directly from keratinocytes and fibroblasts. Using a 3-D wound model with primary keratinocytes grown on human de-epidermized dermis, we show that MfSAP1 protease can potentially interfere with wound re-epithelization in an acute wound model. Taken together, our work demonstrates that Malassezia proteases have host-associated substrates and play important roles in cutaneous wound healing.